(untitled) (Biological Sciences - PJSIR, 1998)
Low grade jute fibres are mainly used for sacking weft batches. In processing technology these fibres draw least attention of the millers. In the present work enzymes were used to improve the softening of hard fibres for further processing. The enzymes were extracted by fermenting indigenous wheat bran as substrate with the fungi, Aspergillus spp. The carding effect was improved by introducing higher pin density at the sacking finisher card. By pretreatment with A terreus enzyme, 36.37% jute cutting was used in hessian weft batch which reduced the batch cost without impairing yarn quality and production efficiency. Moreover, the use of modified finisher card improved the yarn quality of both, the enzyme treated and untreated batches.